(untitled) (The Planet, 2024)
Introduction: Renal insufficiency or chronic kidney disease (CKD) is a predictor of in-hospital outcome after coronary artery bypass grafting (CABG). It is well established that the presence and progression of cardiovascular disease and CKD are often intimately associated. Historically, the shift towards off-pump coronary artery bypass (OPCABG) grafting was proposed to avoid the deleterious effects of the contact of blood with the artificial extracorporeal circuit (i.e., mainly the systemic inflammatory response and coagulopathy). Objectives: To assess the in-hospital outcome of Off Pump CABG in patients with impaired renal function. Methods & Materials: This prospective observational study was conducted in Department of Cardiac Surgery, United Institute of Cardiovascular Science (UICVS), Dhaka. Sampling technique was purposive sampling. Ethical approval was obtained from the institute ethical review board. Patients of significant coronary artery disease underwent CABG were selected. Then study population were allocated into two groups- group-A, (patients with renal insufficency, e-GFR ≤60 ml/min/1.73 m2) and group-B (patients free from renal dysfunction, eGFR of >60 ml/min/1.73 m2). Post operatively follow-up was done and in-hospital outcome was evaluated. Data was processed and analysed with the help of computer program SPSS and Microsoft excel. Result: Mean age was found 54.6±8.3 years. Male and female ratio was 2.8:1. Study shows that 105(82.0%) of the patients recovered without any complication, among them 75.0% patients in group-A and 89.0% patients in group-B. In group-A, 12.5% had developed acute kidney injury, but none of case detected AKI in group-B. Other outcomes between groups were statistically non-significant. Conclusion: Present study concluded that major morbidities were found similar in both groups. Only post-operative AKI was significant finding in CKD patients, others were non-significant between groups.